Using Facebook - Rutledge, Patrice-Anne (Que, 2011)
"Using Facebook is more than just a book: It's the fastest, easiest way to make the most of Facebook! You won't just "read" about it: You'll see it, hear it, live it, with step-by-step video tutorials and valuable audio sidebars. Get comfortable with Facebook! It's all here, including finding and communicating with friends (old and new) ... controlling your privacy and visibility ... posting new messages, photos, video, and links ... using Chat and Email to communicate privately ... joining (or creating) a group ... discovering great events (or creating your own) ... promoting your business, organization, or brand ... shopping on Facebook ... improving your page with new applications ... checking out what your kids are up to ... even getting help finding your next job! Exclusive online Show Me video walks through tasks you've just got to see ... Tell Me More audio delivers practical, "straight from the experts" insights. It's all the help you'll ever need ... where you want it, when you want it!"--Resource description page.